Community Knowledge and Practices for Malaria Prevention: A Cross-sectional Study on Tribal Adults in Bangladesh.: Community Knowledge and Practices for Malaria Prevention - Chakma, Anirban; Niloy, Lamiya Tasnim; Aktaruzzaman, M M; Orchi, kreetika; Nurunnabi, Mohammad; Gupta, Mithun; Hossain, Irin (Journal of the Medical College for Women & Hospital, 2025)
Background: Malaria is a major public health concern in Bangladesh, with ethnic minorities in the Chittagong Hill Tracts (CHTs) being highly vulnerable due to forest-based occupations and poor housing. Aim: This study aims to find out the current state of knowledge and practices on the prevention of malaria among tribal adults in Bangladesh. Materials and Method: A community-based cross-sectional study was carried out from January to December 2022 in the Rangamati district, Bangladesh. Data were collected from 234 conveniently selected tribal adults through face-to-face interviews using a semi-structured questionnaire. Results: Knowledge of malaria transmission and prevention was generally high, with 96.6% identifying mosquito bites as the cause and 99.1% recognizing it as preventable. Most (97.9%) knew preventive measures, and long lasting insecticide treated Net (LLINs) were widely known (96.6%), though none were owned or used. Misconceptions persisted, with 30.8% attributing malaria to poor cleanliness. Symptom recognition was inconsistent, with fever and shivering (60.7%) most common, while awareness of intermittent fever, sweating, and convulsions were low. Vulnerable groups such as pregnant women (67.1%) and children (44.4%) were better recognized than the elderly (30.8%) or people with chronic disease (1.3%). Prevention practices relied mainly on environmental control: cleaning surroundings (98.7%), vegetation clearance (73.1%), and land levelling (54.7%); while personal protective measures (21.8%) were less used. The absence of LLIN access, despite high awareness, highlights the need for improved distribution and targeted health education. Conclusion: The study highlights strong general awareness of malaria transmission and prevention among the respondents, with widespread knowledge of LLINs despite none owning them. Environmental management practices are well adopted, but personal protective measures and recognition of less common symptoms and vulnerable groups remain limited. J Med Coll Women Hosp.2025; 21 (2):91-101